The need for improved management of status epilepticus in children in Australia: Time from seizure onset to treatment is consistently delayed. (16th August 2021) - Uppal, Preena; Cardamone, Michael; Fonseca, Bob; Briggs, Nancy; A Lawson, John
Abstract : Aim: To determine if the management of paediatric status epilepticus (SE) follows accepted clinical practice guidelines. Methods: Retrospective, consecutive series of patients with SE who attended the emergency departments from two NSW sites over a 12‐month period. SE was defined as a convulsive seizure, 5 min or more in duration. Time to presentation to the ED, time to first‐ and second‐line treatment, number of benzodiazepine (BZD) doses given prior to intubation and adherence to guidelines were evaluated. The outcomes included seizure duration, need for respiratory support, admission to intensive care, morbidity and mortality. Results: The time from onset of seizure to ED presentation was a median (p25–p75) time of 22 (15–40) min. Forty‐eight of 59 presentations received pre‐hospital midazolam. The median (p25–p75) time to first‐line treatment was 15 (8–25) min and to second‐line treatment was 43.5 (35–59) min. There was no significant difference in the results in the two hospitals. The total number of BZD doses ranged from 1 to 7 (median 3). There was non‐adherence to the clinical practice guidelines in 55 (93.2%) of 59 presentations. Conclusions: We found excessive benzodiazepine use and delay in both definitive treatment of status epilepticus and in escalation from first‐ to second‐line anticonvulsant treatment. This raises the need for rapid escalation of treatment. We propose a 'status epilepticus code' for emergency departments.